Prediction of Gas‐Phase Acidities of Strong Brønsted Acids by ONIOM Method. Issue 2 (11th October 2021) - Fukaya, Haruhiko; Ono, Taizo; Sonoda, Takaaki; Mishima, Masaaki
Abstract: The gas‐phase acidities of very strong neutral Brønsted acids are estimated based on Gaussian theory and two‐layer ONIOM calculations. Although the calculated gas‐phase acidities using Gaussian theory are in excellent agreement with the experimental values, these high‐level calculations are limited to small molecules because of their high computational cost. ONIOM calculation with the smallest model system, where only the acid center is placed in the high layer, gives relatively poor results. In contrast, ONIOM calculation with a model system expanded to neighbor atoms or the next neighbor atoms of the acid center gives estimates of gas‐phase acidities with practically useful accuracy. Abstract : The gas‐phase acidities of Brønsted acids were estimated using two‐layer ONIOM calculations. Three sizes of the model system were examined, namely a system with only the acid center placed in the high layer (ONIOM1), one that additionally included neighbor atoms of the acid center (ONIOM2), and one that additionally included next neighbor atoms (ONIOM3). ONIOM1 calculation gives relatively poor results, whereas ONIOM2 and ONIOM3 give usefully accurate estimates of gas‐phase acidities.